(untitled) (Cardiovascular Journal, 2015)
Objective: This study tried to elucidate the role of the cardiopulmonary bypass on the early postoperative immunoglobulin G levels and any probable effects on the postoperative outcome of the patients. Methods: 99 consecutive patients were studied. The evening after surgery the level of the immunoglobulin G was obtained. The postoperative course of each patient during the first three days was followed. One way ANOVA was used for statistical analysis. Results: 20 (20.2%) patients had decreased early postoperative immunoglobulin G levels. 87 (87.87%) patients were operated with cardiopulmonary bypass and 17 (19.54%) of them had lower levels of postoperative immunoglobulin G without any significantly increased clinically adverse events. The statistical analysis between the two groups included: pulmonary infiltrations, leukocytosis >15x103/mm3, pulmonary dysfunction, mechanical ventilation >24h, renal and hepatic dysfunction, postoperative ileus, postoperative delirium, sternal wound infection, thrombocytopenia <60x103/ mm3 and sepsis. The statistical results were: p=0.815, p=0.88, p=0.93, p=0.30, p=0.67, p=0.13, p=0.84, p=0.38, p=0.76 respectively. Conclusion: In this pilot study we tried to explore the role of cardiopulmonary bypass on the early postoperative levels of immunoglobulin G and to establish any correlation with the postoperative outcome. The use of cardiopulmonary bypass and its duration did not prove to be risk factors for low early postoperative immunoglobulin G levels. In our opinion the prophylactic use of IVIG in this group of patients has no benefit. DOI: http://dx.doi.org/10.3329/cardio.v7i2.22247 Cardiovasc. j. 2015; 7(2): 79-84